Nocturnal Fabulations: Ecology, Vitality and Opacity in the Cinema of Apichatpong Weerasethakul - Bordeleau, Érik (Immediations, 2017)
Nocturnal Fabulations is an essay in intercessing. This is not a book that is simply 'about' Apichatpong Weerasethakul, though it does engage his work in detail. It is a book that deeply questions what else might be at stake in setting up the conditions for collaboration across two genres: cinema and writing. This collective project is animated by a shared curiosity in the pragmatics of fabulation and its speculative gesture of bringing forth a people to come. In an encounter with Apichatpong's cinematic dreamscape, the concepts of ecology, vitality and opacity emerge to articulate an ethos of fabulation that deframes experience, recomposes subjectivity and unfixes time.